A cohort study of serum 25-hydroxyvitamin D levels and the risk of hyperlipidaemia in adults - Liu, Zi-yue; Liu, Sha; Yao, Xue; Wang, Chun-yang; Song, Yunhao; Bi, Yan-ming; Wang, Jin-Xiu; Li, Yang; Shi, Ta-la; Mi, Wei; Chen, Caiyun; Hu, Zhi-Yong (Frontiers in Nutrition, 2025)
Objective: This study aims to investigate the potential association between serum 25(OH)D levels and the risk of hyperlipidemia in adults through a prospective cohort study conducted in Zhejiang Province. Methods: Baseline surveys and follow-up studies were conducted to collect and analyze follow-up data over a three-year period. Vitamin D deficiency was defined as 25(OH)D < 20 ng/mL, insufficiency as 20-29 ng/mL, and sufficiency as 25(OH)D ≥ 30 ng/mL. Hyperlipidemia or dyslipidemia was defined as the presence of hypercholesterolemia, hypertriglyceridemia, or both. The relationship between demographic characteristics and the incidence of hyperlipidemia among the study participants was explored. Results: A total of 1,210 participants were included in this study, with 43.80% being male. The mean age of the participants was 51.84 ± 14.37 years, and the average serum 25(OH)D level was 25.89 (21.50, 29.82) ng/mL. A significant difference in the proportion of vitamin D deficiency was observed between males and females (22.06% vs 10.94%, P < 0.001). Vitamin D deficiency and insufficiency were prevalent among the middle-aged and elderly population (78.24%). Significant differences were found between the two groups in multiple sociodemographic variables, behavioral factors, and metabolic risk factors (P < 0.05). The incidence of hyperlipidemia among vitamin D-deficient individuals was 1.612 times higher than that among vitamin D-sufficient individuals (95% confidence interval [CI]: 1.228-2.116; P < 0.001). After fully adjusting for confounding factors, the multivariate-adjusted hazard ratio (HR) was 1.572 (95% CI: 1.187-2.08; P = 0.002), indicating a difference in the incidence of hyperlipidemia across different serum vitamin D levels.This cohort study reveals a significant association between serum 25(OH)D levels and the incidence of hyperlipidemia. Additionally, lifestyle factors associated with vitamin D deficiency are also correlated with the incidence of hyperlipidemia. These findings provide further evidence for improving blood lipid profiles through adjustments in vitamin D intake or related lifestyle modifications.